2013
DOI: 10.5194/bg-10-119-2013
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of nitrogen budgets for contrasting catchments at the landscape scale

Abstract: Abstract.A comprehensive assessment of nitrogen (N) flows at the landscape scale is fundamental to understand spatial interactions in the N cascade and to inform the development of locally optimised N management strategies. To explore these interactions, complete N budgets were estimated for two contrasting hydrological catchments (dominated by agricultural grassland vs. semi-natural peat-dominated moorland), forming part of an intensively studied landscape in southern Scotland. Local scale atmospheric dispers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 57 publications
4
10
3
Order By: Relevance
“…2 NH3 emitted to the atmosphere is either deposited directly or transformed into an ammonium aerosol (e.g., ammonium nitrates and ammonium sulfate) often transported over long distances. 3 Two types of NHx (NH3 (gas) + NH4 + (aerosol)) deposition usually occur: dry deposition of NH3 close to the emission sources, 4,5 and wet deposition of NH4 + that can occur at far distances downwind from the sources. 6 N biogeochemical cycles follow the principle of mass balance, and the Nr input to and output from the atmosphere system are normally balanced.…”
Section: Introductionmentioning
confidence: 99%
“…2 NH3 emitted to the atmosphere is either deposited directly or transformed into an ammonium aerosol (e.g., ammonium nitrates and ammonium sulfate) often transported over long distances. 3 Two types of NHx (NH3 (gas) + NH4 + (aerosol)) deposition usually occur: dry deposition of NH3 close to the emission sources, 4,5 and wet deposition of NH4 + that can occur at far distances downwind from the sources. 6 N biogeochemical cycles follow the principle of mass balance, and the Nr input to and output from the atmosphere system are normally balanced.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing nitrogen budgets at the ecosystem scale can be an indicator of environmental pressures, with the determination of stock quantities and dynamics of Nr fluxes between air, soil and water, providing important information for designing effective environmental regulations for mitigating environmental pressures (Vogt et al, 2013). Although complete C budgets for bogs are now common in the literature (Billett et al, 2010;Moody et al, 2018;Nilsson et al, 2008;Worrall et al, 2018), comprehensive N budgets have received comparatively little attention.…”
Section: Introductionmentioning
confidence: 99%
“…While overall the system was found to be a sink of 1.9 kg N ha −1 y −1 , for 4 years the system acted as a net source of N, suggesting a transition from net N sink to net source. Similarly, Vogt et al (2013) and Drewer et al (2010) concluded that a moorland catchment in southern Scotland is showing signs of nitrogen saturation, defined as ecosystem N losses being equal or exceeding N inputs (Butterbach-Bahl et al, 2011), with a negative N balance of −1.6 to −2.4 kg N ha −1 y −1 . Despite a relatively low atmospheric N deposition rate (3.3 kg N ha −1 y −1 ) in a northern Minnesota bog, it was found that more than twice as much N was exported than received (Hill et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of nutrient input-output budgets as a method for evaluating the impacts of anthropogenic activities on the fluvial environment has long been recognized (Crisp, 1966;Winter et al, 2002;Cooper, 2005;Rothwell et al, 2008;Vogt et al, 2013). Freshwater acidification from high atmospheric sulphur (S) and inorganic nitrogen (N) deposition is a major water quality problem in many upland environments in the Northern Hemisphere (Stoddard et al, 1999;Curtis et al, 2000;Evans et al, 2000;Aherne et al, 2003;Skjelkvale et al, 2003).…”
Section: Introductionmentioning
confidence: 99%